Evaluation of Implants, Clover, and Fescue Variety on Stocker Steers – Year 2 - J. K. Farney; M. Frahm; S. Strnad; T. Bottorff (Kansas Agricultural Experiment Station Research Reports, 2022)
Sixty-four growing steers were used in a split-plot experiment, where the whole plot was pasture, and the split-plot was the implant level. Whole plot treatment was a 4 × 2 factorial with four levels of fescue (High Endophyte, Low Endophyte, Novel, or Endophyte Free) and two levels of legume (Legumes or No Legumes). The split-plot included four implant levels (No Implant, Synovex One Grass, Revalor-G, or Ralgro). Data collected were weights, hair coat scores, hair length, rectal temperature (every 28 days), and ultrasound carcass characteristics when steers were coming off grass. Steers on High Endophyte had the lowest average daily gain (ADG) and final weight and smallest loin muscle as compared to steers on all other fescue types. The gain differentiation was observed beginning at day 56 through the end of the study. Overall, ADG was not impacted by the addition of legume. Steers that were implanted with Synovex One Grass had a greater gain, final weight, and lower hair score as compared to non-implanted steers. For many of the other measures, steers implanted with Ralgro or Revalor-G resulted in changes between non-implanted steers and those receiving Synovex One Grass. Steers on high endophyte fescue had greater final weight and ADG than non-implanted steers or those receiving Ralgro, with Synovex One Grass being intermediate. Gains for steers on endophyte free pastures were also impacted by the type of implant where Synovex One Grass steers had greater gains than non-implanted and Revalor-G steers, with Ralgro being intermediate. In this second year of research, the use of low to no endophyte fescue and the addition of implants increased gains.
Keywords: fescue toxicity; growth; gain; endophyte-free; non-toxic